2019
DOI: 10.21037/atm.2019.07.17
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis between lymphoma-associated malignant pleural effusion and tuberculous pleural effusion

Abstract: Background: Lymphoma-associated malignant pleural effusions (L-MPE) can mimic tuberculous pleural effusion (TPE) characterized by lymphocytic exudate with high adenosine deaminase (ADA) levels. Furthermore, the low cytological yield of L-MPE makes differentiation between L-MPE and TPE more challenging. However, there are few data regarding differential diagnosis of L-MPE and TPE. Methods: All consecutive patients diagnosed with L-MPE or TPE between January 2011 and December 2016 were retrospectively recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 35 publications
6
19
0
Order By: Relevance
“…In our study, 10.7% of TPE cases had a histological confirmation of TB, which was similar to a South Korean study showing that 13.9% of patients had a positive histological diagnosis of TPE [ 21 ]. Of interest, while there is little evidence in the literature about using cytological examination for diagnosing TPE, a high proportion of our study participants (43.0%) were confirmed to have TPE cytologically.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, 10.7% of TPE cases had a histological confirmation of TB, which was similar to a South Korean study showing that 13.9% of patients had a positive histological diagnosis of TPE [ 21 ]. Of interest, while there is little evidence in the literature about using cytological examination for diagnosing TPE, a high proportion of our study participants (43.0%) were confirmed to have TPE cytologically.…”
Section: Discussionsupporting
confidence: 90%
“…Among our study participants, eight (4.3%) were confirmed to have a malignant disease. The proportion of presumptive TPE with cancer varies from 7.3% to 55.4% across the published literature [ 21 , 22 , 23 ]. The differences between our study and the other studies are explained by the specific study populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This level was much higher than ADA levels previously reported in lymphoma cases with pleural effusion and tuberculous pleural effusion cases. 1 Our case and review of the literature suggests the possibility that pleural effusate ADA levels in patients with PEL-LL might be much higher than those in patients with other types of lymphomas and those with tuberculous pleural effusion. More data are needed to validate our observation.…”
Section: Discussionmentioning
confidence: 66%
“…Tuberculous pleural effusion and lymphoma are included in the differential diagnosis of patients with high adenosine deaminase (ADA) levels in pleural effusate. Previous reports showed that median ADA levels in pleural fluid were 73 IU/L (interquartile range 44‐124 IU/L) and 84 IU/L (interquartile range 64‐110 IU/L) in patients with lymphoma‐associated malignant effusion (n = 17) and tuberculous pleural effusion (n = 216), respectively 1 . Our patient with primary effusion lymphoma (PEL)–like lymphoma (PEL‐LL) had extremely high ADA levels in pleural fluid.…”
Section: Introductionmentioning
confidence: 97%